2016
DOI: 10.3389/fonc.2015.00303
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Coverage of the Lower Limb following Oncological Surgery

Abstract: The treatment of lower limb tumors has been shifted by advancements in adjuvant treatment protocols and microsurgical reconstruction from limb amputation to limb salvage. Standard approaches include oncological surgery by a multidisciplinary team in terms of limb sparing followed by soft tissue reconstruction and adjuvant therapy when indicated. For the development of a comprehensive surgical plan, the identity of the tumor should first be determined by histology after biopsy. Then the surgical goal and compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…In traumatic cases, longer vascular pedicles are often required to place the microvascular anastomoses outside of the zone of injury [1]. Reconstruction with well-vascularized free tissue transfer for lower extremity reconstruction after oncological resection proved safe and effective in patients undergoing postoperative radiation therapy [6,23]. Free flap reconstruction has led to advances in limb-sparing resection of tumors of the lower extremities [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In traumatic cases, longer vascular pedicles are often required to place the microvascular anastomoses outside of the zone of injury [1]. Reconstruction with well-vascularized free tissue transfer for lower extremity reconstruction after oncological resection proved safe and effective in patients undergoing postoperative radiation therapy [6,23]. Free flap reconstruction has led to advances in limb-sparing resection of tumors of the lower extremities [24].…”
Section: Discussionmentioning
confidence: 99%
“…Local flaps provide similar tissue characteristics, thickness, and weight-bearing capacity to the reconstructed areas [3]. Microsurgical free flap reconstruction is widely established in traumatic and non-traumatic lower extremity defects and was proven to be safe in patients of advanced age, although the patients suitability to undergo extended surgeries needs to be explored [4][5][6]. The timing of reconstructive surgery is influenced by multiple factors including the patients' general state and the contamination of the wound; however, in traumatic defects, early free tissue transfer was associated with less complications than delayed reconstruction [7].…”
Section: Introductionmentioning
confidence: 99%
“…The literature does not report a significant difference between reconstruction and amputation in primary cases [9]. Surgical treatment has moved in the direction of reconstructive interventions [3]. However, it has been suggested that in cases of recurrence or pathological fractures, or when the tumor cannot be removed surgically, amputation is more effective in the local control of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Because of technological advances and increasing experience in oncological treatment, there have been significant developments in the treatment of these patients and survival rates have become higher [2]. When the literature is reviewed, it can be seen that surgical treatment by amputation has become less prevalent than limb salvage surgery since the 1990s as a result of good results reported following reconstruction [3]. The purpose of limb salvage surgery is to maintain the functions of the extremity and to remove the local disease completely.…”
mentioning
confidence: 99%
“…The optimum approach to the prevention of wound problems is the careful preoperative planning of soft tissue reconstruction, sand their performance in the same session as the resection . One of the most commonly used methods to be applied when wound problems occur is Negative Pressure Wound Therapy (NPWT), which creates a pressure gradient between the wound and the suction through a direct effect.…”
Section: Introductionmentioning
confidence: 99%